Analysis of plantar impact characteristics of walking in patients with flatfoot according to basic mechanical features and continuous wavelet transform - Bai, Xiaotian; Huo, Hongfeng; Lu, Peng; Luan, Yisheng; Koga, Ami; Liu, Jingmin (Frontiers in Physics, 2022)
Flatfoot is a common foot deformity, and the collapse of the arch structure affects the foot cushioning during walking. A growing number of scholars have found that the analysis of the impact force should be combined with both the magnitude and the frequency of the impact force. Therefore, the aim of this study is to investigate the plantar impact characteristics of flatfoot patients and normal foot people at different load-bearing buffer stage from the time and frequency domains. Sixteen males with flatfoot and sixteen males with normal foot were recruited to walk on the plantar pressure test system at the same step speed, and the vertical ground reaction force data were collected from the heel contact stage and the arch support stage. The differences in the frequency domain of the ground reaction force between the flatfoot and the normal foot in the two stages were analyzed according to the basic mechanical characteristics and the continuous wavelet transform. 1) In terms of basic mechanical characteristics, In both groups for flatfoot patients and normal foot people, the peak ground reaction force was higher in the arch support stage compared to the heel contact stage (P<0.001, P<0.001), and the load rate of force change was smaller in this stage (P<0.001, P<0.001). In the arch support stage, the force change load rate of patients with flatfoot was lower than that of normal foot people (P=0.021). 2) The results of time and frequency domain characteristics showed that during the heel contact and the arch support stage, compared with the foot heel contact stage, the maximum signal power in the arch support stage was higher (P < 0.001, P<0.001), and the corresponding impact frequency was smaller (P=0.002, P=0.004). Once the step speed was controlled, the flatfoot patients only showed a smaller impact force load rate in the arch support stage, which may be related to their lower arch rigidity. The characteristics of the impact force in different stages of walking support period were different in time and frequency domain, suggesting that there may be differences in the function of various parts of the foot.